Effects of energy supply and nicotinic acid supplementation on phagocytosis and ROS production of blood immune cells of periparturient primi- and pluriparous dairy cows. (February 2018) - Bühler, S.; Frahm, J.; Liermann, W.; Tienken, R.; Kersten, S.; Meyer, U.; Huber, K.; Dänicke, S.
Abstract: Effects of energy supply and nicotinic acid (NA) supplementation on the phagocytic activity of polymorphonuclear leukocytes (PMN) and peripheral blood mononuclear cells (PBMC), and on ROS production in PMN of periparturient cows differing in parity were examined. 29 pluriparous and 18 primiparous cows were allocated to four different feeding groups from 42 days prepartum until 100 days postpartum. They were fed either a ration with a low concentrate proportion of 30% (LC) or a high concentrate proportion of 60% (HC). After parturition all animals received 30% concentrate which was increased to 50% either within 16 (LC) or within 24 days (HC). The different concentrate feeding strategies aimed at triggering differences in postpartum lipolysis. Half of the animals per group were supplemented with 24 g per day of NA from 42 days prepartum until 24 days postpartum. All investigated parameters varied significantly over time compared to parturition ( p  < 0.05). Numbers of phagocytosing PMN and PBMC increased in the course of the experiment, whereas the amount of engulfed bacteria per cell decreased between 42 and 11 days prepartum. Percentage of basal ROS producing PMN decreased strongly before parturition and reached initial values only at 28 days in milk again. Mean fluorescence intensity (MFI) in these ROS producing cells, however, increased before parturition. Oxidative burst stimulation in PMN was reduced around parturition but the amount of ROS produced in the stimulated cells was increased. Pluriparous cows exhibited higher numbers of basal ROS producing PMN and phagocytic PBMC. NA supplementation influenced phagocytosis in blood leukocytes. Highlights: Time courses of phagocytic activity of PMN and PBMC and ROS production in PMN throughout the periparturient period. Comparison of the functional capacity of blood leukocytes between primi- and pluriparous cows. Functional activity of blood leukocytes is significantly influenced by parturition but not only impaired.